2009
DOI: 10.1095/biolreprod.109.076000
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potentially Damaging Amino Acid Substitutions Leading to Human Male Infertility1

Abstract: There are a number of known genetic alterations found in men with nonobstructive azoospermia, or testicular failure, such as Y microdeletions and cytogenetic abnormalities. However, the etiology of nonobstructive azoospermia is unknown in the majority of men. The aim of this study was to investigate the possibility that unexplained cases of nonobstructive azoospermia are caused by nonsynonymous single-nucleotide polymorphisms (SNPs) in the coding regions of autosomal genes associated with sperm production and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 39 publications
0
10
0
1
Order By: Relevance
“…Our laboratory recently found a large cluster of non-synonymous substitutions in the SBF1 gene in men suffering from testicular failure (Kuzmin et al 2009). SBF1, or MTMR5, is a pseudophosphatase, and interacts with the histone methyltransferase SUV39H.…”
Section: Discussionmentioning
confidence: 99%
“…Our laboratory recently found a large cluster of non-synonymous substitutions in the SBF1 gene in men suffering from testicular failure (Kuzmin et al 2009). SBF1, or MTMR5, is a pseudophosphatase, and interacts with the histone methyltransferase SUV39H.…”
Section: Discussionmentioning
confidence: 99%
“…A third potential sex determining gene is sbf1 (SET binding factor 1), a member of the protein-tyrosine phosphatase family involved in cell growth and differentiation which is highly expressed in the brain and testes. Alterations in the sbf1 sequence or splicing lead to male infertility, impaired spermatogenesis and azoospermia in humans, mice and rats [56][57][58][59]. Notably, sbf1 is nested in the 7 million base pair chromosomal region, enriched with X-specific genes in S. scincus.…”
Section: Cytogenetic Analysismentioning
confidence: 99%
“…It was suggested that certain genome sections may tend to be recruited for the function of sex chromosomes, or be added later as a part of neo-sex chromosomes, non-randomly more often than other parts due to the content of genes involved in gonad differentiation (e.g. amh, dmrt1, sox3) and sex-specific traits [50][51][52][53][54][55][56][57][58][59][60][61][62]. It is true that some syntenic blocks were co-opted for the role of sex chromosomes across amniotes several times, for example the ortholog of GGAZ in birds, in a turtle lineage, and twice independently in geckos, the ortholog of GGA4p which makes up the main part of the sex chromosomes in viviparous mammals, geckos of the genus Paroedura and lacertid lizards [22], and GGA28 in anguimorphan lizards and monotremes [18].…”
Section: Cytogenetic Analysismentioning
confidence: 99%
“…Disorganized tubules, reduced sertoli and germ cells, no mature sperm produced [Print et al 1998] [Kuzmin et al 2009] …”
Section: Fkbp6 Knockout Mouse Modelmentioning
confidence: 99%